Stability and Turnover of the ACTH Receptor Complex - Clark, Adrian J. L.; Chan, Li (Frontiers in Endocrinology, 2019)
Glucocorticoid production in mammals is principally regulated by the action of the pituitary hormone adrenocorticotropin (ACTH) acting on its cognate membrane receptor on the zona fasciculata cells of the adrenal cortex. The receptor for ACTH consists of two essential components, a small seven transmembrane domain G protein-coupled receptor of the melanocortin receptor subgroup known as the melanocortin 2 receptor (MC2R) and a small single transmembrane domain protein that adopts a antiparallel homodimeric form and which is known as the melanocortin 2 receptor accessory protein (MRAP). MRAP is essential for the trafficking of the MC2R to the cell surface as well as being required for receptor responsiveness to ACTH at physiological concentrations – probably by facilitating ACTH binding, but possibly also by supporting G protein interaction with the MC2R. A number of studies have shown that ACTH stimulates the expression of functional receptor at the cell surface and the transcription of both MC2R and MRAP mRNA. However the time course of these transcriptional effects differs such that MRAP is expressed relatively rapidly whereas MC2R transcription responds much more slowly. Furthermore, recent data suggests that MRAP protein is turned over with a short half-life whereas MC2R has a significantly longer half-life. These findings imply that these two ACTH receptor proteins have distinct trajectories and that it is likely that MRAP-independent MC2R is present at the cell surface. In such a situation newly transcribed and translated MRAP could enable the rapid recruitment of functional receptor at the plasma membrane without the need for new MC2R translation. This may be advantageous in circumstances of significant stress in that the potentially complex and perhaps inefficient process of de novo MC2R translation, folding, post-translational modification and trafficking can be avoided.